Implementation of Blockchain as Covid-19 Test and Vaccine Certificate Storage System - Arya Raditya Prawira Putra, Dendi; Purwanto, Yudha; Paryasto, Marisa (Universitas Telkom, 2022)
The existence of the Covid-19 virus, which was first announced at the end of 2019, in a short time was able to cause a pandemic. To overcome this, the government implemented a protocol that integrates Covid-19 test results and vaccination certificates into an application, with the aim that individuals can prove that they are free from Covid-19 infection and can return to normal activities. However, a centralized system is prone to single point of failure and data manipulation from the intervention of certain parties due to a lack of transparency. This paper proposed the use of Ethereum blockchain and smart contracts to solve this problem. By Using blockchain technology and smart contracts, the data management process will be more transparent since every transaction on the blockchain is recorded by each node. Blockchain also prevents a single point of failure because there are more than one data providers. The system that has been developed has fulfilled the security and privacy aspects of patient data by implementing password-based encryption on patient data. However, the system’s response time is strongly influenced by the computational capabilities of the Rinkeby network. On average, the system took 47,9 seconds to register a new certificate.